ANALISIS PENDAPATAN PEKERJA WANITA PADA HOME INDUSTRY ANYAMAN TAS PLASTIK DI DESA SETAIL - Wayan Sudirman, Nur Faidatuz Zuhroh, (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2020)
Home based plastic braided bag is an industry that produces products by emphasizing the function of use with various motifs and sizes, as well as the selection of models, raw materials and colors that can support the quality of the products produced. The purpose of this study was to analyze the effect of work experience, number of dependents, raw materials and product demand on the income of female workers. The research sample were 80 respondents. Data was collected using observation, questionnaires and interviews. Moderated Regression Analysis was used. The results of the study showed that work experience, number of dependents, raw materials, and product demand partially and simultaneously had  significant effect on the achievement of female workers. Work experience with product demand has a negative and significant effect on Home-based plastic braided bag industry in Setail Village, Banyuwangi Regency.